If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(1) + y = 5 Multiply -4 * 1 -4 + y = 5 Solving -4 + y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + y = 5 + 4 Combine like terms: -4 + 4 = 0 0 + y = 5 + 4 y = 5 + 4 Combine like terms: 5 + 4 = 9 y = 9 Simplifying y = 9
| 2z=-82 | | -4(0)+y=5 | | 0.15+0.5x=0.4 | | 6x^2-13x=28 | | 6z^2-7z-20=0 | | -8+11s=12s | | .05x+.20(100)=.1(100+x) | | -2+y=6 | | 0.5x-1=1.5 | | 4r+7r=88 | | 6-3x=5x-10x+10 | | 75x^2-91x-12= | | x^1-5x=0 | | -7+y=-3 | | -57=6+9x | | 4+y=-3 | | -3s=-51 | | x-(-12)=-17 | | 14x-42=56 | | y-3=x | | 5-10y=-9y | | x^2=-10x-9 | | x^2-x-42=0 | | 5(t+3)+9=3(p-2)+6 | | x^2-24x+114=0 | | X^2=3x+7 | | 3x-2y=18 | | 13=10-z | | -6x^2-25x-25=0 | | 4t^2+33t+54=0 | | -13=-26 | | 50-4Q=2 |